Cost-Effective Thermal-Insulating Building Materials - Noriega, Salvador (2020)
We report on the development of a formula for an adequate mix of aggregates to produce concrete blocks, which, while preserving high mechanical resistance, show good thermal insulation and reduced production costs. Three aggregates with different proportions were compared, consisting of pumice, wood shavings and basalt; the amounts of each material were 1800, 1970 and 2150 kg. A three-factor experimental design was applied to statistically determine the best factors for the response variables, namely, a high compression resistance and low thermal conductivity. The best mix obtained is composed of 250 kg of cement, 1970 kg of pumice and three amounts of sand with minor differences.